Chronic Enteropathy and Vitamins in Dogs - Yu Tamura (Animals)
Chronic enteropathy (CE) or chronic inflammatory enteropathy is a group of diseases with multiple and different etiologies characterized by chronic gastrointestinal signs such as vomiting, diarrhea, anorexia, weight loss for more than 3 weeks, and inflammatory cell infiltration, such as lymphoplasmacytic cells in the intestinal mucosal lamina propria. The diagnosis was histologically confirmed after excluding other diseases such as parasitic infections, tumors, pancreatitis, exocrine pancreatic insufficiency, metabolic diseases, and endocrine diseases, such as hypoadrenocorticism. Nutritional management depends on several important functions, such as digestion and absorption processes, digestive enzymes and nutritional transporters, and barrier functions. Intestinal dysbiosis may have been found to be involved in various functions. Recently, cobalamin (vitamin B12) and vitamin D have been considered negative prognostic factors in dogs with CE. Cobalamin supplementation ameliorates clinical disease severity in dogs with CE, and vitamin D supplementation ameliorates hypocalcemia in dogs with CE and hypoalbuminemia. Therefore, the aim of this review is to provide an overview of CE and present treatment and nutritional management strategies for CE and prognostic vitamins.